2022
DOI: 10.3390/microorganisms10020314
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses of Weissella cibaria W25, a Potential Bacteriocin-Producing Strain Isolated from Pasture in Campos das Vertentes, Minas Gerais, Brazil

Abstract: Weissella is a genus containing Gram-positive, heterofermentative bacteria belonging to the lactic acid bacteria (LAB) group. These bacteria are endowed with promising technological and antimicrobial attributes. Weissella cibaria W25 was isolated from a dairy environment where raw milk cheeses are produced. Therefore, we sequenced and assembled the W25 draft genome sequence, which consists of 41 contigs totaling ~2.4 Mbp, with a G + C content of 45.04%. Then we carried out a comprehensive comparative genomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Culture-independent approaches including PCR-DGGE and next-generation sequencing approaches such as metagenetics and metagenomics have allowed the detection of weissellas in various ecological niches ( Table 2 ). Whole-genome sequencing is another approach that is being widely used to identify and characterize weissellas (Benomar et al, 2011 ; Kim et al, 2011 ; Amari et al, 2012 ; Lee J. H. et al, 2012 ; Figueiredo et al, 2014a , b , 2015 ; Tanizawa et al, 2014 ; Malik et al, 2016 ; Heng et al, 2017 ; Ku et al, 2017 ; Li et al, 2017 ; Du et al, 2018 ; Garcia-Cancino et al, 2019 ; Kwak et al, 2019 ; Panthee et al, 2019 ; Lin et al, 2020 ; Månberger et al, 2020 ; Baugh et al, 2021 ; Contente et al, 2021 ; Jang et al, 2021 ; Patrone et al, 2021 ; Yuan et al, 2021 ; Apostolakos et al, 2022 ; Fanelli et al, 2022 ; Fukuda and Nolasco-Hipolito, 2022 ; Surachat et al, 2022 ; Teixeira et al, 2022 ).…”
Section: Detection and Typing Of Weissellamentioning
confidence: 99%
See 1 more Smart Citation
“…Culture-independent approaches including PCR-DGGE and next-generation sequencing approaches such as metagenetics and metagenomics have allowed the detection of weissellas in various ecological niches ( Table 2 ). Whole-genome sequencing is another approach that is being widely used to identify and characterize weissellas (Benomar et al, 2011 ; Kim et al, 2011 ; Amari et al, 2012 ; Lee J. H. et al, 2012 ; Figueiredo et al, 2014a , b , 2015 ; Tanizawa et al, 2014 ; Malik et al, 2016 ; Heng et al, 2017 ; Ku et al, 2017 ; Li et al, 2017 ; Du et al, 2018 ; Garcia-Cancino et al, 2019 ; Kwak et al, 2019 ; Panthee et al, 2019 ; Lin et al, 2020 ; Månberger et al, 2020 ; Baugh et al, 2021 ; Contente et al, 2021 ; Jang et al, 2021 ; Patrone et al, 2021 ; Yuan et al, 2021 ; Apostolakos et al, 2022 ; Fanelli et al, 2022 ; Fukuda and Nolasco-Hipolito, 2022 ; Surachat et al, 2022 ; Teixeira et al, 2022 ).…”
Section: Detection and Typing Of Weissellamentioning
confidence: 99%
“…Teixeira et al ( 2022 ) sequenced the genome of W. cibaria W25, isolated from a Brazilian pasture samples of a Brazilian dairy farm, and found that this strain had the possibility of producing two different bacteriocins. Thereafter, the same authors (Teixeira et al, 2023 ) demonstrated a putative bacteriocinogenic activity of W. cibaria W25 against Salmonella enterica Newport, Kocuria rhizophila, Listeria innocua , and E. coli strains.…”
Section: An Update Of the Probiotic Potential Of Weissella ...mentioning
confidence: 99%
“…The genome sequence of the W25 strain was previously deposited in GenBank under accession number JAFNKE000000000 (Teixeira et al, 2022). The whole genomes of W. cibaria W21 and W42 were sequenced, trimmed, and assembled as recently performed for the W25 strain (Teixeira et al, 2022).…”
Section: Genome Sequencing Assembly and Annotationmentioning
confidence: 99%
“…The genome sequence of the W25 strain was previously deposited in GenBank under accession number JAFNKE000000000 (Teixeira et al, 2022). The whole genomes of W. cibaria W21 and W42 were sequenced, trimmed, and assembled as recently performed for the W25 strain (Teixeira et al, 2022). Gene prediction and annotation were performed using the Rapid Prokaryotic Genome Annotation (PROKKA) v. 1.14.5 (Seemann, 2014), executed with default parameters, and also performed by RAST automated web server (Aziz et al, 2008).…”
Section: Genome Sequencing Assembly and Annotationmentioning
confidence: 99%
See 1 more Smart Citation